Derechas, neoliberalismo y estereotipos de género. La revista Veja de Brasil, 1989-1999 - Verónica Giordano (Nuevo mundo - Mundos Nuevos, 2017)
The period 1989-1999 is crucial to study the social and cultural changes that accompanied the implementation of the Washington Consensus and State Reform and had a more long-winded range.We aim to study gender stereotypes built by the Brazilian right during the decade of neoliberal boom. We look at Veja covers. The magazine is a product of Editora Abril, with long experience in the Brazilian cultural market. Created in April 1950, it was consolidated as a powerful multimedia group during the nineties, expressing the common sense of most rancid right forces.In the period 1989-1999, the ideas concerning gender equality agenda entered the building of the social order of the right forces to the extent that some issues that were previously considered very marginally, or even silenced or censored, became topics of public debate. But we must note that it did not occurred uniformly in all spheres, for ideas relating to the women`s performance of executive positions in the State remained impregnated of traditionalism.